Short-term Curcuminoid Supplementation for Chronic Pulmonary Complications due to Sulfur Mustard Intoxication: Positive Results of a Randomized Double-blind Placebo-controlled Trial - Panahi, Y; Ghanei, M; Bashiri, S; Hajihashemi, A; Sahebkar, A (Drug research, 2015)
Pulmonary problems are among the most frequent chronic complications of sulfur mustard (SM) intoxication and are often accompanied by deregulated production of pro-inflammatory cytokines. Curcuminoids, comprising curcumin, demethoxycurcumin and bisdemethoxycurcumin, are phytochemicals with remarkable anti-inflammatory properties that are derived from dried rhizomes of the plant Curcuma longa L. (turmeric). The present pilot study aimed to investigate the clinical effects of supplementation with curcuminoids on markers of pulmonary function and systemic inflammation in SM-intoxicated subjects. In a randomized double-blind placebo-controlled trial, 89 male subjects who were suffering from chronic SM-induced pulmonary complications were recruited and assigned to either curcuminoids (500 mg TID per oral; n=45) or placebo (n=44) for a period of 4 weeks. Efficacy measures were changes in the spirometric parameters (FVC, FEV1, FEV1/FVC) and serum levels of inflammatory mediators including interleukins 6 (IL-6) and 8 (IL-8), tumor necrosis factor-α (TNFα), transforming growth factor-β (TGFβ), high-sensitivity C-reactive protein (hs-CRP), calcitonin gene related peptide (CGRP), substance P and monocyte chemotactic protein-1 (MCP-1). 78 subjects completed the trial. Although FEV1 and FVC remained comparable between the groups, there was a greater effect of curcuminoids vs. placebo in improving FEV1/FVC (p=0.002). Curcuminoids were also significantly more efficacious compared to placebo in modulating all assessed inflammatory mediators: IL-6 (p<0.001), IL-8 (p=0.035), TNFα (p<0.001), TGFβ (p<0.001), substance P (p=0.016), hs-CRP (p<0.001), CGRP (p<0.001) and MCP-1 (p<0.001). Curcuminoids were safe and well-tolerated throughout the trial. Short-term adjunctive therapy with curcuminoids can suppress systemic inflammation in patients suffering from SM-induced chronic pulmonary complications.